2021
DOI: 10.1021/acs.jpca.1c01211
|View full text |Cite
|
Sign up to set email alerts
|

Relative Strengths of a Pnicogen and a Tetrel Bond and Their Mutual Effects upon One Another

Abstract: The ability of the T and Z atoms of TR3ZR2 to engage in a noncovalent interaction with NH3 is assessed by DFT calculations, where the T atom refers to C, Si, and Ge; Z = As, Sb, and P; and substituents R = H and F. In most instances, the tetrel bond (TB) is both stronger and shorter than the pnicogen bond (ZB). These two bond strengths can be equalized, or preference shifted to the ZB, if F substituents are placed on the Z and H on the T atoms. Employing C as the T atom results in a very weak TB, with the ZB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 104 publications
0
16
0
Order By: Relevance
“…[21] Zierkiewicz et al [22] studied the tetrel bonding interactions between various pyridine with tetrahedral tetrel compounds TF 4 (T=Si, Ge, Sn) at MP2/cc-pVTZ level and obtained two different conformers of the complexes: axial and equatorial conformer. Meanwhile , Scheiner [23] compared interactions through tetrel bond (N … T) and pnicogen bond (N … Z) in the complexes between TR 3 ZR 2 (T = C, Si, Ge, Z = P, As, Sb and R = H, F) and NH 3 and concluded that tetrel bonded complexes are stronger than the pnicogen bonded one. Wei et al [24] studied the N … T tetrel bonded complexes between metal cyanides (MCN, M=Cu, Ag and Au) and TF 4 (T=C, Si, Ge and Sn) at MP2/ aug-cc-pVTZ level and predicted that the Ag substituent has the highest enhancing effect on the interaction energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Zierkiewicz et al [22] studied the tetrel bonding interactions between various pyridine with tetrahedral tetrel compounds TF 4 (T=Si, Ge, Sn) at MP2/cc-pVTZ level and obtained two different conformers of the complexes: axial and equatorial conformer. Meanwhile , Scheiner [23] compared interactions through tetrel bond (N … T) and pnicogen bond (N … Z) in the complexes between TR 3 ZR 2 (T = C, Si, Ge, Z = P, As, Sb and R = H, F) and NH 3 and concluded that tetrel bonded complexes are stronger than the pnicogen bonded one. Wei et al [24] studied the N … T tetrel bonded complexes between metal cyanides (MCN, M=Cu, Ag and Au) and TF 4 (T=C, Si, Ge and Sn) at MP2/ aug-cc-pVTZ level and predicted that the Ag substituent has the highest enhancing effect on the interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…studied the tetrel bonding interactions between various pyridine with tetrahedral tetrel compounds TF 4 (T=Si, Ge, Sn) at MP2/cc‐pVTZ level and obtained two different conformers of the complexes: axial and equatorial conformer. Meanwhile , Scheiner [23] compared interactions through tetrel bond (N … T) and pnicogen bond (N … Z) in the complexes between TR 3 ZR 2 (T=C, Si, Ge, Z=P, As, Sb and R=H, F) and NH 3 and concluded that tetrel bonded complexes are stronger than the pnicogen bonded one. Wei et al [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed an explosive growth in the study of noncovalent bonds that are close parallels of the venerable H-bond. In each of the chalcogen, pnicogen, tetrel, and triel bonds, an atom of that same particular family of the periodic table replaces the bridging proton of the H-bond. Among these interactions, the halogen bond (XB) is arguably the one that has been acknowledged for the longest time and has engendered the greatest amount of scrutiny. Extensive study has demonstrated that the XB owes its stability to several factors. In the first place, the electron-density cloud surrounding the X atom is quite anisotropic; while the overall charge on the X atom is partially negative, there is a pocket of positive potential that lies along the extension of the covalent C–X bond, which is commonly referred to as a σ-hole.…”
Section: Introductionmentioning
confidence: 99%
“…However, the required distortion to a planar unit so as to form such π‐holes was also much more energetically costly. The Si··NH 3 σ‐hole tetrel bond interaction energy of SiF 3 SbF 2 is 37 kcal/mol 86 and that for SiF 3 Cl is 36 kcal/mol 87 …”
Section: Summary and Discussionmentioning
confidence: 99%